Dexmedetomidine for the prevention of emergence delirium and postoperative behavioral changes in pediatric patients with sevoflurane anesthesia: a double-blind, randomized trial - Shi M; Miao S; Gu T; Wang D; Zhang H; Liu J (Dove Medical Press, 2019)
Mengzhu Shi,1,* Shuai Miao,1,* Tianchu Gu,1 Dongyue Wang,1 Hui Zhang,1 Jindong Liu2 1Jiangsu Province Key Laboratory of Anesthesiology, Xuzhou Medical University, Xuzhou, Jiangsu, China; 2Department of Anesthesiology, The Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, China *These authors contributed equally to this work Objectives: Emergence delirium (ED) is a common neurologic complication that can not only distress children and their families in the early postanesthetic period, but can also have adverse effects on children in the long-term. This study aimed to investigate the effects of single-dose dexmedetomidine on ED in children with sevoflurane anesthesia and to observe postoperative behavioral changes through long-term follow-up.Methods: Patients aged 2–7 years, American Society of Anesthesiologists class (ASA) I or II, scheduled for tonsillectomy with and without adenoidectomy were randomized to receive dexmedetomidine 0.5 µg/kg (Group D) or volume-matched normal saline (Group C) over 10 minutes after induction of anesthesia. The primary outcome was the incidence of ED within 30 minutes after extubation. Other outcomes were the incidence of pain, extubation time, post-anesthesia care unit (PACU) length of stay after extubation, adverse events, and the incidence of negative postoperative behavioral changes (NPOBCs).Results: Ninety children completed the study. Compared with the control group (Group C), dexmedetomidine decreased the incidence of ED (31.1% vs 53.3%; P=0.033) and pain (28.9% vs 57.8%; P=0.006), but it prolonged extubation time (P<0.001). PACU length of stay after extubation and the percentage of adverse events were similar between groups. The incidence of NPOBCs in Group D was significantly lower at 1 and 7 days after discharge (33.3% vs 60.0%; P=0.011% and 24.4% vs 46.7%; P=0.028, respectively) than it was in Group C, but no significant difference was found at the 30th day.Conclusion: Dexmedetomidine 0.5 µg/kg reduced the incidence of ED after sevoflurane anesthesia and might be used to prevent NPOBCs.Clinical trials registration: ChiCTR1800016828. Keywords: dexmedetomidine, emergence delirium, postoperative behavioral changes, tonsillectomy